About Intuition in Analytic Theories of Law - Maciej Dybowski (Avant, 2018)
Contemporary analytic theories of law attempt to provide hermeneutic answers to the metaphysical question about the nature of law with intuition playing a pivotal role in these attempts. It is doubtful, however, whether intuition can meet metaphysical and hermeneutic expectations of such theories. The article points out divergent ways of understanding intuition in analytic theories of law. Moreover, such theories face a dilemma of choosing between the „hard” ontology of law, to which intuition would have a privileged epistemic access, and „soft” ontology which entails multiple types of intuition. If collective consciousness, to which the intuitions that constitute the concept of law allegedly belong, is indeed the metaphysical foundation of contemporary analytic theories, they are hardly discernible from empiricism. A promising complementary approach to such a way of theorizing about law—where the vocabulary of intuitions is prioritized—can be provided by analytic pragmatism extending analysis to the practices in which words acquire their meanings.